1,2-migrations onto gold carbene centers - Wang, Tao; Hashmi, A. Stephen K. (Chemical reviews, 2021)
Gold carbenes are highly active intermediates in homogeneous gold catalysis, enabling a large array of transformations such as C-H/X-H insertions, cyclopropanations, and 1,2-migrations. Unlike C-H/X-H insertions and cyclopropanations, 1,2-migrations onto gold carbene centers seem to be attracting less attention. There has been no comprehensive review focusing on this topic, even though this chemistry has become a powerful tool for the rapid and simple construction of molecular complexity. This review provides comprehensive and critical information on the 1,2-migrations onto gold carbene centers, drawing a preliminary conclusion on the migratory aptitude of various groups. The review is divided into several parts according to the kind of carbene precursors.
Published: October 7, 2020
Gesehen am 30.09.2021